(untitled) (Scientific journal of the Fergana State University, 2025)
The article analyzes the characteristics of the education system in Germany. Germany’s education system has a federal structure, with each of the country’s 16 federal states (Bundesländer) having its own education policy and governance system. The article explores how regional characteristics and their influence on education management are shaped, and how the educational system is governed in these federal states. It also examines how this regional governance ensures effective and equitable education. The article covers the main features of the system, its legal and pedagogical aspects, methods of managing educational institutions, as well as the degree to which education is connected with social, cultural, and economic factors. It compares traditional and modern aspects of regional governance, as well as centralized and decentralized governance. The article provides detailed information about innovations in education, teacher training and professional development, differences in educational curricula, and the social and cultural implications of these differences. Finally, the article concludes with an assessment of the successful aspects of the education governance system in Germany, regional disparities, innovations in education, and the impact of global educational trends.